The influence of social support on hematopoietic stem cell transplantation survival: a systematic review of literature. - Sara Beattie; Sophie Lebel; Jason Tay (PLoS ONE, 2013)
Background Hematopoietic Stem cell Transplantation (HSCT) can negatively impact the psychosocial well-being of the patient. Social support is a complex term that has been variably used to encompass perceived and objective support, including caregiver presence. Social support has been associated with superior psychosocial outcomes; however the influence of social support on HSCT survival remains unclear. We sought to summarize the literature on the influence of social support on HSCT survival. Methods MEDLINE, EMBASE, COCHRANE, CINAHL, AND PSYCINFO WERE SEARCHED USING THE FOLLOWING SEARCH CATEGORIES/CONCEPTS: 1) HSCT, 2) Social support, 3) Caregiver, 4) Survival, and 5) Treatment outcomes. Results We identified 6 relevant studies: 4 publications, 1 dissertation, and 1 abstract. Three studies were retrospective and 3, prospective. Sample size ranged between 92-272 with a mean/median patient age between 30-55 yrs. The duration of follow-up ranged between 13.3-48 months. Social support was measured inconsistently: 2 by retrospective investigator assessment, 2 as patients' perceived support, 1 as caregiver presence, and 1 included caregiver presence and retrospective investigator assessment. The 4 published studies and 1 abstract demonstrate an association between better social support and survival. However, the unpublished dissertation, with the largest sample size found no association. Conclusions There is a paucity of evidence examining social support with HSCT survival. Available studies are older, with the most recent publication in 2005. A heterogeneous group of HSCT patients were studied with variable follow-up times. Further, covariates were variably considered in HSCT survival analyses and we suggest that there may be publication bias, given the negative unpublished study with the largest sample size. Prospective studies using validated scales are necessary to better assess the influence of social support on HSCT mortality. Given the potential for improved HSCT survival with better social support, HSCT centres should routinely provide HSCT recipients and their caregivers with enhanced psychosocial services.